2020
DOI: 10.1155/2020/2931097
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phytochemical Profile, Mineral Content, andIn VitroAntioxidant Activities ofCorchorus capsularisandCorchorus olitoriusLeaf Extracts from Different Populations

Abstract: In addition to fiber, Corchorus (jute) leaf is also rich in secondary metabolites and is used in folk medicine in jute-producing communities. It has been reported that jute halts progression of and helps manage different chronic diseases like tumors, obesity, diabetes, and cardiovascular diseases. Various phytochemical, mineral, and antioxidant potency properties of 30 genotypes belonging to Corchorus capsularis and Corchorus olitorius were evaluated in the current study. The results demonstrate that the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
4
24
0
Order By: Relevance
“…Likewise, the strong correlation between FRAP assay and total phenolic of other antioxidants has been reported [44]. The number and arrangement of hydroxyl groups, as well as the existence of electron donating and electron withdrawing substituents in the ring structure of phenolics, decide their antioxidant capacity [49,50]. These results showed that polysaccharides and total phenolic content play an important role in the measured antioxidant properties of kenaf leaves, although the degree of correlation suggests that other factors could also contribute.…”
Section: Correlation Between Antioxidant Capacities With Polysaccharide Total Phenolic and Flavonoid Contentmentioning
confidence: 91%
“…Likewise, the strong correlation between FRAP assay and total phenolic of other antioxidants has been reported [44]. The number and arrangement of hydroxyl groups, as well as the existence of electron donating and electron withdrawing substituents in the ring structure of phenolics, decide their antioxidant capacity [49,50]. These results showed that polysaccharides and total phenolic content play an important role in the measured antioxidant properties of kenaf leaves, although the degree of correlation suggests that other factors could also contribute.…”
Section: Correlation Between Antioxidant Capacities With Polysaccharide Total Phenolic and Flavonoid Contentmentioning
confidence: 91%
“…The Folin-Ciocal method was used to determine total tannins [11]. 1 mL of leaf extract was mixed with 49 mL of purified water, 1.7 ml of 75 percent ethanol, 0.1 ml metaphosphoric acid, 1.0 mol/ml Na2CO3 (10 ml), and 2.5 ml Folin-Ciocalteu in a volumetric flask (100 ml).…”
Section: Tanninmentioning
confidence: 99%
“…Concerning the nutritional properties of C. olitorius leaves, the main critical element is represented by the consumption habits that involve boiling the leaves. In the case of C. olitorius , recent data showed that the total polyphenols content of fresh leaves ranges from 5.41 to 7.78 mg GAE/g DW depending on the genotype ( 40 ). Considering these reference values, our data suggest that boiling reduced the amount of polyphenols by at least 55–65%.…”
Section: Discussionmentioning
confidence: 99%